PENGARUH OLAHRAGA AEROBIK PAGI DAN MALAM HARI TERHADAP KADAR LEUKOSIT REMAJA PUTRI DI ASRAMA UNIVERSITAS NEGERI MALANG - Fachrurrozi Ainur Rofiq; Rias Gesang Kinanti; Olivia Andiana (Universitas Negeri Malang, 2018)
Abstract Regular and measurable exercise with moderate to moderate exercise intensity can improve health, body fitness and immunity. These exercises can increase the body's resistance to the incidence of infection, whereas exercise with maximum intensity and exhaustion can cause impaired immunity. Regular and sustained exercise with the right dose in a certain time can improve functional work in the body. So this research would like to know if there is influence of aerobic exercise conducted in the morning and evening to the leukocyte level of young women. This research uses quasi experiment nonequivalent group design. The sample in this study used young girls age 18-20 years in dormitory State University of Malang. The instrument used for data collection is Horiba ABX research. The exercises are moderate intensity aerobic exercise with 16 meetings, then the samples are taken with 3cc of blood with rest for 24 hours before the blood is taken. The result of the research is based on data analysis using ANOVA test and t-test of data that between the differences of the two groups is not found there is a significant difference, that is Sig. > α or 0.381> 0.005. The conclusion of this study is that there is no significant effect on leukocyte level after being treated by morning and night aerobic exercise.Keywords: Aerobic Sports, Morning and Night, leukocyte.